UNSEEN AND UNTOUCHED: NARRATIVES OF DISCRIMINATION AGAINST MANUAL SCAVENGERS IN KASHMIR - Majid, Sana; Altaf, Sakina; Bhat, Yasir Hamid (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Unnoticed in the larger political narrative over Kashmir is the fact that manual scavengers still perform this work because of their caste, even though it has been banned by law. This study looks at what it is like for manual scavengers in the Sheikh and Wattal communities in Srinagar, whose job, which is called tchh paajun, is influenced by age-old caste systems. Nine in-depth interviews reveal that people face social ostracism, name-calling and the negative effects handed down through several generations. Participants explain that the way people speak and the culture’s influence subjugate them into caste-based hierarchies, and their gender further adds to their vulnerability. Regardless of the problems they face, many parents believe education can give their children freedom and honour. The result from the research suggests that there is a large disconnect between the laws abolishing caste work and the reality on the ground, so more sensitive and well-suited local efforts to tackle this issue are needed in Kashmir